Estimation of the Al Metal-Puff Density Profile on the Generator GIT-12; Energy Fluxes and Radiation Effects (EFRE-2020 online) - Cherdizov R. Rustam; Kokshenev V. Vladimir; Shishlov A. Alexander; Baksht R. Rina; Oreshkin V. I. Vladimir Ivanovich; Rousskikh A. Alexander; Zhigalin A. Alexander (2020, 2020)
Title screen